Pengaruh Likuiditas, Profitabilitas, Free Cash Flow, dan Kinerja Perusahaan Terhadap Stock Return - Putri, Agnes Hana; Bangun, Primsa (Manajemen Bisnis Kompetensi, 2019)
The purpose of this research is to examine the influence of Liquidity, Profitability, Free Cash Flow, and Firm Performance on Stock Return of companies listed in LQ 45 for the period 2013-2016. This research used samples 24 companies listed in LQ 45 and selected the samples using judgement sampling method. The dependent variable of this research is Stock Return, meanwhile the independent variables are Liquidity, Profitability, Free Cash Flow, and Firm Performance. Data processing in this research using software program Eviews (Econometric Views) 10. The result of this research shows that Liquidity and Profitability have a significance influence on Stock Return while Free Cash Flow and Firm Performance have no significance influence on Stock Return.Keywords: Liquidity, Profitability, Free Cash Flow, Firm Performance, Stock Return